Physical education teachers’ reality and experience from teaching during a pandemic - López-Fernández, Iván; Gil-Espinosa, Francisco Javier; Burgueño, Rafael; Calderón, Antonio (Taylor & Francis, 2023)
Most physical education (PE) research pertaining to COVID-19 has focused on the (negative) implications and difficulties PE teachers face during this pandemic period. In fact, despite informed calls for reform and radical change in PE, little attention has been paid to the (potentially positive) implications for teachers’ pedagogical practices and, more importantly, for the future of PE. Drawing on a social constructivism theoretical perspective, this paper explores the reality from several PE teachers’ perspectives and reflects on the type of PE that the global pandemic conditioned. We approached this analysis informed by Lawson, H. A. (2009. Paradigms, exemplars and social change. Sport, Education and Society, 14(1), 97–119.) and Quennerstedt, M. (2019. Physical education and the art of teaching: Transformative learning and teaching in physical education and sports pedagogy. Sport, Education and Society, 24(6), 611–623.) calls for the PE community to (re)act and drive PE to its twenty-first century version. Using methods associated with a process-oriented methodology, this study adopted a cross-sectional qualitative design, and 12 PE teachers with diverse backgrounds and teaching experiences participated. We conducted a series of semi-structured interviews that began with the following question: ‘How can the experience of blended or online PE contribute to the improvement of current and future PE?’ To analyse the data, an amalgamation of inductive and deductive approaches was used. Three major themes were constructed: (1) impact: PE teachers reinventing themselves to allow PE to continue being educative; (2) resilience: learning and flourishing together to overcome the challenge and improve the PE system; and (3) selective expansion: more physical activity (PA) and digital technology.

We concluded that the COVID-19 pandemic has agitated the foundations of PE as a field, creating a scenario in which teachers show high levels of collegiality and improved readiness to overcome current and future challenges.This could be another stage of the PE journey towards community aspirations (whatever they could be).
https://openpolicyfinder.jisc.ac.uk/id/publication/6107
Keywords: Profesores de educación física; Educación física - Estudio y enseñanza; Investigación activa en educación; Pandemic; Covid-19; Physical education; Teaching